2022
DOI: 10.3389/fspor.2022.1037078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 6 week core strengthening training on measures of physical and athletic performance in adolescent male sub-elite handball players

Abstract: The objective was to investigate the effects of a 6-week core strengthening training within the regular handball training sessions compared to regular handball training only. Male sub-elite handball players were randomly assigned to an intervention (INT: n = 13; age: 16.9 ± 0.6 years) or a control (CON: n = 13; age: 17.2 ± 0.8 years) group. The INT group performed the “big 3” core exercises cross curls-up, side bridge (both sides), and the quadrupedal stance (“birddog exercise”) triweekly for 20–30 min while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As a matter of fact, studies conducted in other sports have yielded varied results regarding the impact of core exercises on sport-specific parameters. In one such study examining the effects of core strengthening training on physical and athletic performance in elite handball players, significant improvements were observed in physical components, but not in handball-specific athletic performance [ 14 ]. Similarly, a study investigating the effects of core exercises on functional movement patterns in adult tennis players reported significant changes in all functional movement screen test results [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, studies conducted in other sports have yielded varied results regarding the impact of core exercises on sport-specific parameters. In one such study examining the effects of core strengthening training on physical and athletic performance in elite handball players, significant improvements were observed in physical components, but not in handball-specific athletic performance [ 14 ]. Similarly, a study investigating the effects of core exercises on functional movement patterns in adult tennis players reported significant changes in all functional movement screen test results [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of core stability training (CST) on athletic performance has been and continues to be studied. Previous studies revealed that a CST program increased some parameters of general performance and sportspecific performance in badminton, handball, baseball, basketball, football, swimming, tennis, rhythmic gymnastics, and modern dance [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Cross is an attack pattern that relies on short and long crosses with moderate intensity playing patterns [9]. Cross play patterns can be started from any position, either from the left and right wing, flashlight and pivot or from left back and right back positions.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, studies conducted in other sports have yielded varied results regarding the impact of core exercises on sport-specific parameters. In one such study examining the effects of core strengthening training on physical and athletic performance in elite handball players, significant improvements were observed in physical components, but not in handballspecific athletic performance [14]. Similarly, a study investigating the effects of core exercises on functional movement patterns in adult tennis players reported significant changes in all functional movement screen test results [48].…”
Section: Plos Onementioning
confidence: 99%